2020
DOI: 10.21203/rs.3.rs-124421/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facilitators and barriers to Pre-Exposure Prophylaxis (PrEP) uptake among adolescent girls and young women in Seme-Sub County, Kisumu, Kenya

Abstract: Background: While the introduction of HIV pre-exposure prophylaxis (PrEP) as an HIV prevention strategy has allowed women to exercise more control over the reduction of HIV transmission rates, adolescent girls and young women (AGYW) in Sub-Saharan Africa continue to experience higher rates of HIV infections and bear the greatest disease burden. Understanding progress in PrEP uptake among AGYW would enhance risk reduction in this vulnerable population. The Determined, Resilient, AIDS-Free, Mentored and Safe wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Throughout SSA, PrEP is being added to public health systems that are already resource‐constrained, resulting in challenges for provider buy‐in [48–50]. Providers in our study, however, demonstrated their willingness to change how they deliver PrEP, even if this meant taking on additional work.…”
Section: Discussionmentioning
confidence: 86%
“…Throughout SSA, PrEP is being added to public health systems that are already resource‐constrained, resulting in challenges for provider buy‐in [48–50]. Providers in our study, however, demonstrated their willingness to change how they deliver PrEP, even if this meant taking on additional work.…”
Section: Discussionmentioning
confidence: 86%
“…Overall, the community rollout of PrEP in the DREAMS Initiative was successful due to a number of key enabling factors, which ultimately led to successful PrEP implementation, increased PrEP initiation, and improved persistence among adolescent girls and young women. The barriers identified must be addressed so that a larger scale of PrEP rollout can take place in the future (Jackson-Gibson et al, 2021).…”
Section: Explaining the Factors That Influence The Knowledge Gap Abou...mentioning
confidence: 99%